2012
DOI: 10.1186/1749-799x-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term functional outcome after the internal fixation of distal radius fractures

Abstract: BackgroundDistal radius fracture is a common injury with a variety of operative and non-operative management options. There remains debate as to the optimal treatment for a given patient and fracture. Despite the popularity of volar locking plate fixation, there are few large cohort or long term follow up studies to justify this modality. Our aim was to report the functional outcome of a large number of patients at a significant follow up time after fixation of their distal radius with a volar locking plate.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 36 publications
2
47
1
1
Order By: Relevance
“…15 In their large series of 170 patients with distal end radius fractures, Kanabar et al noticed that parameters such as range of motion and grip strength were regained by up to 94% in the three months after volar plating. 16 Also, the shorter the trauma surgery interval and better achievement of volar tilt resulted in better functional outcome as also found in study by Phadnis et al 17 The overall complication rate in our study was 18%, which is comparable to that reported by Jagodzinski et al in a bicentric study on distal radius variable angle locking plates. 18 They reported a complication rate of 19.6%, although the majority had screw misplacement, while Kawasaki et al had no reported cases of screw misplacement.…”
Section: Discussionsupporting
confidence: 87%
“…15 In their large series of 170 patients with distal end radius fractures, Kanabar et al noticed that parameters such as range of motion and grip strength were regained by up to 94% in the three months after volar plating. 16 Also, the shorter the trauma surgery interval and better achievement of volar tilt resulted in better functional outcome as also found in study by Phadnis et al 17 The overall complication rate in our study was 18%, which is comparable to that reported by Jagodzinski et al in a bicentric study on distal radius variable angle locking plates. 18 They reported a complication rate of 19.6%, although the majority had screw misplacement, while Kawasaki et al had no reported cases of screw misplacement.…”
Section: Discussionsupporting
confidence: 87%
“…While in Anakwe RE, et al average time of bony union was 12 weeks. 25 Overall mean time to fracture union was 8.4 weeks (6-28 weeks) in the study of Phadnis J et al 32 Excessive distraction of the hardware to obtain satisfactory reduction can result in delayed union nonunion complex regional pain syndrome or digital stiffness. 33,34 Avoidance of malunion is important, since a poor anatomical result adversely affects recovery of function as was reflected in the difficulties patients with malunion had with activities of daily living.…”
Section: Discussionmentioning
confidence: 98%
“…Joideep Phadnis et al [11] 133 patients (74%) had post-operative radiographs available for analysis. Overall mean time to fracture union was 8.4 weeks (6-28 weeks) shows time to union by fracture type.…”
Section: Time Of Unionmentioning
confidence: 99%